Trabalho, saúde e educação: um estudo sobre a formação profissional dos agentes comunitários de saúde do estado do Maranhão no período 2004-2011 - Monteiro, Maria Alcina Gomes de Sousa (2013)
This study discusses about Health Professional Education in the current economic, political and social in presenting educational projects which, under the logic of capital, are geared to adapt to the needs of workers and capitalists others who point to the construction of critical able to understand the foundations and contradictions of capitalist production process of questioning and forms of exploitation they are subjected. The objective is analyze the proposed formation of Community Health Workers in the state of Maranhão in the period from 2004 to 2011, to understand the impacts on professional practice and working conditions in this category. The methodology is based on the use of bibliographic references on the subject and document analysis and is justified by allowing a rethink about the recent practice of training workers SUS, carried out by the SUS In this article we discuss the relationship between health, work and education seen through the prism and ontological and historical context of capitalist sociality in which this relationship takes on new contours as it becomes predominant character merchandising. It presents historical and legal elements of the construction of the professional category of Community Health Workers and the proposed formation for these workers. With an insight into the formation of community health workers of the state of Maranhão. An unfinished project on cyclical conditions that has allowed these workers to conclude this process of training and professionalization.